2007
DOI: 10.1111/j.1524-4725.2007.33223.x
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology-Based Presurgical Management for Nonmelanoma Skin Cancer: A Pilot Study

Abstract: SFTD has been demonstrated to be effective and accurate as a preoperative tool for nonmelanoma skin cancer, avoiding unnecessary visits to the hospital and shortening the waiting intervals to the surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 15 publications
2
40
0
1
Order By: Relevance
“…67 Time to surgery or definitive intervention was significantly shorter in the 3 studies that reported this outcome. 9,67,68 The difference ranged from 21 to 86 days (all P \.01). Two studies reported time to teledermatology results.…”
Section: Question 3: Clinical Outcomesmentioning
confidence: 94%
See 4 more Smart Citations
“…67 Time to surgery or definitive intervention was significantly shorter in the 3 studies that reported this outcome. 9,67,68 The difference ranged from 21 to 86 days (all P \.01). Two studies reported time to teledermatology results.…”
Section: Question 3: Clinical Outcomesmentioning
confidence: 94%
“…Teledermatology patients required a mean of 0.98 visits in one study 67 and one visit in another study. 9 In the same two studies, clinic dermatology patients required a mean of 1.13 or at least 2 visits, respectively.…”
Section: Question 3: Clinical Outcomesmentioning
confidence: 97%
See 3 more Smart Citations